Meta-analysis of the effect of learning cycle model on students’ physics learning outcomes - Festiyed Festiyed; Annisa Fadilla; Desnita Desnita; Murtiani Murtiani (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2023)
Many studies related to the influence of the learning cycle model on learning outcomes have been carried out, but a summary of this topic needs to be related. This research aims to determine the summary effect of the learning cycle model on physics learning outcomes in general and review based on class level, subject matter units, types of learning cycle model, and types of learning outcomes. The research method used is a meta-analysis. Two research results can be presented based on the data analysis conducted. First, the effect size of the learning cycle model on students' physics learning outcomes is 0.915 in the high category. Second, the effect of the learning cycle model on student physics learning outcomes has the highest effect on (1) class XI of 0.921, (2) fluid material unit of 1.026, (3) learning cycle model 7E is 0.931, (4) learning outcomes for skills aspects are 1.126.